Acclimation of the crucifer Eutrema salsugineum to phosphate limitation is associated with constitutively high expression of phosphate‐starvation genes. (13th June 2016) - Velasco, Vera Marjorie Elauria; Mansbridge, John; Bremner, Samantha; Carruthers, Kimberley; Summers, Peter S.; Sung, Wilson W.L.; Champigny, Marc J.; Weretilnyk, Elizabeth A.
Abstract: Eutrema salsugineum, a halophytic relative of Arabidopsis thaliana, was subjected to varying phosphate (Pi) treatments. Arabidopsis seedlings grown on 0.05 mm Pi displayed shortened primary roots, higher lateral root density and reduced shoot biomass allocation relative to those on 0.5 mm Pi, whereas Eutrema seedlings showed no difference in lateral root density and shoot biomass allocation. While a low Fe concentration mitigated the Pi deficiency response for Arabidopsis, Eutrema root architecture was unaltered, but adding NaCl increased Eutrema lateral root density almost 2‐fold. Eutrema and Arabidopsis plants grown on soil without added Pi for 4 weeks had low shoot and root Pi content. Pi‐deprived, soil‐grown Arabidopsis plants were stunted with senescing older leaves, whereas Eutrema plants were visually indistinguishable from 2.5 mm Pi‐supplemented plants. Genes associated with Pi starvation were analysed by RT‐qPCR. EsIPS2, EsPHT1 ; 4 and EsPAP17 showed up‐regulated expression in Pi‐deprived Eutrema plants, while EsPHR1, EsWRKY75 and EsRNS1 showed no induction. Absolute quantification of transcripts indicated that PHR1, WRKY75 and RNS1 were expressed at higher levels in Eutrema plants relative to those in Arabidopsis regardless of external Pi. The low phenotypic plasticity Eutrema displays to Pi supply is consistent with adaptation to chronic Pi deprivation in its extreme natural habitat. Abstract : Phosphorus is a limiting macronutrient in many natural habitats and managed agricultural systems. We show that an extremophile crucifer, Eutrema salsugineum (synonymous with Thellungiella salsuginea ), copes with low phosphate (Pi) using strategies different than its close relative, Arabidopsis thaliana . Pi‐starved seedlings and 4‐week‐old plants have reduced Pi content relative to plants fertilized with Pi but otherwise exhibit comparable phenotype and biomass, suggesting that Eutrema has a naturally high capacity to acquire and manage Pi efficiently. Our results are consistent with Eutrema plants anticipating low environmental Pi, a behaviour revealed in part by a constitutive expression of genes identified as Pi starvation responsive in other plants, including Arabidopsis .